2015
DOI: 10.1016/j.jval.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Satisficing: An Analysis of Sequence Effects in Health Valuation

Abstract: Objective This study estimates the effect of sequence on response precision and behavior in health valuation studies. Methods Time trade-off (TTO) and paired comparison responses from 6 health valuation studies—4 US, 1 Spanish, and 1 Dutch—were examined (22,225 respondents) to test whether task sequence influences response precision (e.g., rounding), response changes and median response times. Each study used a computer-based instrument that randomized task sequence among a national sample of adults, age 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Previous studies were inconclusive about the number of tasks that should be included to avoid respondent fatigue. According to Craig et al [ 36 ], neither randomization nor fewer response tasks would affect response precision, a statement that contradicts prior findings [ 37 39 ]. On the other hand, Savage et al [ 40 ] found that respondents suffered fatigue in online surveys with repeated tasks.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies were inconclusive about the number of tasks that should be included to avoid respondent fatigue. According to Craig et al [ 36 ], neither randomization nor fewer response tasks would affect response precision, a statement that contradicts prior findings [ 37 39 ]. On the other hand, Savage et al [ 40 ] found that respondents suffered fatigue in online surveys with repeated tasks.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, limitations common to DCEs are ordering effects, hypothetical bias, and framing effects. First, ordering effects were minimized by randomizing participants to one of the survey versions because randomizing the order of choice tasks and attributes for each participant was not possible in a paper-based survey ( 39 ). Second, the predicted uptake of upper endoscopy was high.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant literature addressing sequence effects, when/how they occur, and implications for welfare estimation (e.g., Boyle, Bishop, and Welsh 1993;Carson and Mitchell 1995;Bateman and Langford 1997;Carson, Flores, and Hanemann 1998;Holmes and Boyle 2005;Day and Prades 2010;Bech, Kjaer, and Lauridsen 2011;Day et al 2012;Craig et al 2015). If each choice task presented to a respondent is presumed to be independent of the other choices in the sequence, then the absence of a sequencing effect is desirable.…”
Section: Number Of Valuation Questionsmentioning
confidence: 99%